Radiation recall pneumonitis in the setting of immunotherapy and radiation: a focused review - Kerri McGovern; Maged Ghaly; Michael Esposito; Keara Barnaby; Nagashree Seetharamu (Future Science OA, 2019)
Radiation recall pneumonitis (RRP) is an entity described as pneumonitis localized to a previously irradiated field after exposure to a systemic agent. It has previously been described in the literature in the context of chemotherapeutic agents as well as certain biologics. With immunotherapy taking a more prominent role in the treatment of several different malignancies and its own baseline risk of pneumonitis, it is important to explore the likelihood of RRP, specifically in those patients who have been previously treated with radiation therapy. The current literature regarding RRP with checkpoint inhibitors is reviewed in this article. Alongside this review, we report a case of RRP after pembrolizumab initiation in a patient in our practice.